Compact holographic refractometer for liquid analysis - Barbosa, E. A. [UNESP]; Silva, D. M. [UNESP] (Optica Publishing Group, 2010)
The construction and performance of a portable holographic refractometer prototype for liquid measurement is described, using multimode red diode lasers as the light source and a photorefractive Bi12TiO20 (BTO) crystal as the holographic storage medium. © OSA / LAOP 2010.